2014
DOI: 10.1111/jfpp.12350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postharvest Application of 1-Methycyclopropene on Storage Behavior of Fresh Tomatoes (S olanum lycopersicum  L.)

Abstract: The present study was conducted on fresh tomatoes (cv. Punjab Ratta) of mature green to breaker stage treated with 1-methycyclopropene (1-MCP) at different concentrations to find out its efficacy on storage behavior at 13 ± 2C and relative humidity (RH) of 85-90%. Data from this study suggested that 1-MCP had no effect on the TSS content of the fruits during the period of storage. Fruits treated with 1-MCP at 180 mg/10 L recorded the lowest physiological loss in weight throughout the storage period compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The cultivation of tomatoes originated in Peru and Ecuador in South America. Tomatoes had been introduced to China during the Ming Dynasty and are currently considered as one of the most important commercial crops planted in all parts of China (Boggala et al, ). The color of a tomato is red; the flesh is tender, juicy, sweet and sour, and tomatoes are often used as a vegetable in a salad or a side dish (Gómez‐Ramírez, Sosa‐Morales, Palou, & López‐Malo, ).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of tomatoes originated in Peru and Ecuador in South America. Tomatoes had been introduced to China during the Ming Dynasty and are currently considered as one of the most important commercial crops planted in all parts of China (Boggala et al, ). The color of a tomato is red; the flesh is tender, juicy, sweet and sour, and tomatoes are often used as a vegetable in a salad or a side dish (Gómez‐Ramírez, Sosa‐Morales, Palou, & López‐Malo, ).…”
Section: Introductionmentioning
confidence: 99%
“…And little is known about how the CI of fruit may be affected by SI. 1‐Methylcyclopropene (1‐MCP), an effective antagonist blocking ethylene receptor, traditionally was applied on storage of fruit to prevent ethylene‐induced ripening and prolong storage periods of fruit (Boggala et al, ). It has been shown that 1‐MCP can ameliorate CI of persimmon, and pineapple (Salvador, Arnal, Monterde, & Cuquerella, ; Selvarajah, Bauchot, & John, ), but some researches indicated that ethylene plays a positive role in reducing CI development in citrus and nectarines (Lafuente, Zacarias, Martínez‐Téllez, Sanchez‐Ballesta, & Dupille, ; Zhou, Dong, Ben‐Arie, & Lurie, ).…”
Section: Introductionmentioning
confidence: 99%